Management of secondary school teachers in enhancing quality education in Kwara State, Nigeria - Abdullahi, Nimota Jibola Kadir (Penerbit Universiti Kebangsaan Malaysia, 2019)
An effective management within educational institutions could enhance the quality of education provided by the institution. This quantitative study determined the perceptions of secondary school principals on the importance of teacher competency, conducive learning environment, curriculum relevance, staff development, supervision and motivation towards the attainment of quality education. Stratified random sampling technique was used to select 175 public secondary school principals from a population of 310 principals in Kwara State, Nigeria, who participated in the study. Data was collected using the Teacher Management and Quality Education Questionnaire (TMQEQ), and analyzed using descriptive statistics. The findings revealed that the principals agreed that teacher competency, conducive learning environment, curriculum relevance, staff development, supervision and motivation are important towards the attainment of quality education. The findings implicate that school administrators should continuously encourage and support teachers to acquire more training and additional qualification. In addition, government and school principals should constantly supervise teachers’ classroom activities in order to stimulate professional growth of teachers as well as put in place appropriate strategies to motivate teachers towards achieving quality education in the public senior secondary schools in Nigeria.